A Descriptive Study On The Method Of Teaching Listening At The Eighth Grade Of Smp Negeri 2 Jatiyoso In 2013/2014 Academic Year - , Triyono; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2015)
This research is to describe the teaching listening conducted by the eighth grade teacher of SMP Negeri 2 Jatiyoso in 2013/2014 academic year. It is conducted to know the method applied by the English teacher in teaching listening specifically the research is to ask the following question: 1) what is the objective of teaching listening? 2) What is the teaching material? 3) What is the teaching learning procedure? 4) What is the technique of teaching listening? The research is a descriptive research. The writer collects the data by observing teaching-learning process, conducting the interview, and documenting some important data that support this research. The data are interview script, field note, syllabus, text book, and lesson plan. The methods of collecting data are observation, interview, and analysing document. The techniques of analyzing data are reduction the data, data analysis, display the data, and conclusion and verification. The results of the research show that the method of teaching listening used by teacher is Inquiry Based Learning, The goal of teaching listening is to help the students in understanding the listening material, Listening material given to the student are descriptive text and recount text, Teaching learning process is implementated by using five steps, namely Observing, Questioning, Associating, Experimenting, Network. Teaching media used by the teacher is from the textbooks Smart Steps for Junior High School and materials from the Internet. Problems faced by the teacher are the teacher inability to manage the class, the student's limited vocabulary, limited media, and the method used by teacher.